Epidemiological links and antimicrobial resistance of clinical Salmonella enterica ST198 isolates: a nationwide microbial population genomic study in Switzerland. Issue 10 (27th October 2022) - Biggel, Michael; Horlbog, Jule; Nüesch-Inderbinen, Magdalena; Chattaway, Marie Anne; Stephan, Roger
Abstract : Salmonella is a leading cause of foodborne outbreaks and systemic infections worldwide. Emerging multi-drug resistant Salmonella lineages such as a ciprofloxacin-resistant subclade (CIP R ) within Salmonella enterica serovar Kentucky ST198 threaten the effective prevention and treatment of infections. To understand the genomic diversity and antimicrobial resistance gene content associated with S. Kentucky in Switzerland, we whole-genome sequenced 70 human clinical isolates obtained between 2010 and 2020. Most isolates belonged to ST198-CIP R . High- and low-level ciprofloxacin resistance among CIP R isolates was associated with variable mutations in ramR and acrB in combination with stable mutations in quinolone-resistance determining regions (QRDRs). Analysis of isolates from patients with prolonged ST198 colonization indicated subclonal adaptions with the ramR locus as a mutational hotspot. SNP analyses identified multiple clusters of near-identical isolates, which were often associated with travel but included spatiotemporally linked isolates from Switzerland. The largest SNP cluster was associated with travellers returning from Indonesia, and investigation of global data linked >60 additional ST198 salmonellosis isolates to this cluster. Our results emphasize the urgent need for implementing whole-genome sequencing as a routine tool for Salmonella surveillance and outbreak detection.